BOUNDARY-LAYER FLOW OF HEAT AND MASS FOR TIWARI-DAS NANOFLUID MODEL OVER A FLAT PLATE WITH VARIABLE WALL TEMPERATURE - Bao, Han-Xiang; Arain, Muhammad; Shaheen, Sidra; Khan, Hasan; Usman, U.; İnç, Mustafa; Yao, Shao-Wen (Vinca Inst Nuclear Sci, 2022)
A numerical study of boundary-layer flow past on a moving flat plate in nanofluid with variable wall temperature and viscous dissipation is presented. The PDE containing model for flow phenomena are transformed to ODE with the aid of appropriate similarity transformations. The transformed equations are then solved numerically by using the built-in bvp4c scheme of MATLAB. After the validation of the scheme, numerical solutions are determined for the temperature and nanoparticle concentration profiles along with physical quantities of interest. The effects of involved parameters such as variable temperature index, Prandtl number, Eckert number, Lewis number, plate moving parameter, thermophoresis motion, and Brownian parameters are examined and reported through graphs and tables
Keywords: boundary-layer flow; moving flat plate; heat and mass transfer; variable wall temperature